(untitled) (The Pakistan Development Review, 1999)
Pakistan continues to suffer from a syndrome of high fiscal deficits and severe incidence of debt. Its annual fiscal deficit has stayed constantly at over 6 percent of GDP especially since 1990 [Pakistan (1997-98)]. The prevalence of such a high fiscal deficit over the years in a row has propelled increased borrowing from both internal and external sources to cover the resource gap. With inadequate improvement in the repayment capacity of the country debt has continued to accumulate at a massive rate. Serving as the cause and effect of each other, the volumes of both the fiscal deficit and debt have soared continuously. The most devastating consequence of high fiscal deficit and soaring debt has been the continuous accrual of massive debt-servicing. In fact, both the debt and debt-servicing have reached unaffordable limits. How to alleviate this situation has become the foremost issue of the country. While complete elimination of all the debt and thereby debt-servicing may not be easy to accomplish in the short run, efforts are needed to systematically bring the fiscal deficit down to a minimum affordable limit. What may be the minimum financeable level of fiscal deficit and how it may be reduced to that level are the issues addressed in this paper.